Effect of Affective Commitment on the Relationship Between Job Satisfaction and Job Performance of Public School Teachers in Yobe State, Nigeria - Ardo, Mohammed Abu; Gurin, Idris Mohammed; Buhari, Mohammed (PT FORMOSA CENDEKIA GLOBAL, 2024)
The main objective of this study is to investigate the mediating effect of affective commitment on the relationship between job satisfaction and teachers’ job performance in Yobe State. Two hypotheses were formulated for testing. The study design used in this research is a survey design. Sample size of 412 was arrived at, after taking into consideration the extent of variability in the population. Data analysis was done using Statistical Package for Social Science (SPSS) and Partial Least Square-Structural Equation Model (PLS-SEM) i.e. Pls3. The questionnaire items were all reported to have some degree of dependability and legitimacy. The results failed to support both the direct and the indirect null hypotheses revealing the empirical evidence that job satisfaction has significant effect on teachers’ job performance. Affective commitment was found to mediate the relationships between job satisfaction, and teachers’ job performance. Furthermore, the study recommend that Government, through it ministry of education should identify various ways that would increase teachers’ affective commitment such as shared value, fairness and trust with the view to improving their job performance.